While browsing on Integral and Series, I found a strange integral posted by @Sangchul Lee. His post doesn't have a response for more than a month, so I decide to post it here. I hope he doesn't mind because the integral looks very interesting to me. I hope for you too. :-)

enter image description here

$$\mbox{How does one prove}\quad \int_{-\infty}^{\infty} {{\rm d}x \over 1 + \left[\,x + \tan\left(\, x\,\right)\,\right]^{2}} = \pi\quad {\large ?} $$

Please don't ask me, I really have no idea how to prove it. I hope users here can find the answer to prove the integral. I'm also interested in knowing any references related to this integral. Thanks in advance.

  • $\begingroup$ Cauchy's integral formula may be the way to go. $\endgroup$ – John Nov 10 '14 at 19:10
  • $\begingroup$ @John I guess so, but dunno how to use it $\endgroup$ – Venus Nov 10 '14 at 19:13
  • 1
    $\begingroup$ I guess we have to split the integral 'around' the singularities of $\tan(x)$ which leads to an infinite sum... I'm not sure whether it converges... $\endgroup$ – Felix Marin Nov 10 '14 at 20:27

Here is an approach.

We may use the following result, which goes back to G. Boole (1857) :

$$ \int_{-\infty}^{+\infty}f\left(x-\frac{a_1}{x-\lambda_1}-\cdots-\frac{a_n}{x-\lambda_n}\right)\mathrm{d}x=\int_{-\infty}^{+\infty} f(x)\: \mathrm{d}x \tag1 $$

with $a_i>0, \lambda_i \in \mathbb{R}$ and $f$ sufficiently 'regular'.

Observe that, for $x\neq n\pi$, $n=0,\pm1,\pm2,\ldots$, we have $$ \cot x = \lim_{N\to +\infty} \left(\frac1x+\frac1{x+\pi}+\frac1{x-\pi}+\cdots+\frac1{x+N\pi}+\frac1{x-N\pi}\right)$$ leading to (see Theorem 10.3 p. 14 here and see achille's answer giving a route to prove it)

$$ \int_{-\infty}^{+\infty}f\left(x-\cot x\right)\mathrm{d}x=\int_{-\infty}^{+\infty} f(x)\: \mathrm{d}x \tag2 $$

with $\displaystyle f(x)=\frac{1}{1+\left(\small{\dfrac\pi2 -x }\right)^2}$.

On the one hand, from $(2)$, $$ \begin{align} \int_{-\infty}^{+\infty}f\left(x-\cot x\right)\mathrm{d}x& =\int_{-\infty}^{+\infty} f(x)\: \mathrm{d}x \\\\ &=\int_{-\infty}^{+\infty}\frac{1}{1+\left(\small{\dfrac\pi2 -x }\right)^2}\: \mathrm{d}x\\\\ &=\int_{-\infty}^{+\infty}\frac{1}{1+x^2}\: \mathrm{d}x\\\\ & =\pi \tag3 \end{align} $$ On the other hand, with the change of variable $x \to \dfrac\pi2 -x$, $$ \begin{align} \int_{-\infty}^{+\infty}\!\!\!f\left(x-\cot x\right)\mathrm{d}x & =\int_{-\infty}^{+\infty} \!\!\!f\left(\dfrac\pi2-x-\tan x\right)\mathrm{d}x \\\\ & =\int_{-\infty}^{+\infty}\frac{1}{1+\left(x+ \tan x \right)^2} \mathrm{d}x \tag4 \end{align} $$ Combining $(3)$ and $(4)$ gives

$$ \int_{-\infty}^{+\infty}\frac{1}{1+\left(x+ \tan x \right)^2} \mathrm{d}x=\pi. $$

  • 3
    $\begingroup$ Jesus, this is brilliant!! +1 But one question (maybe this is stupid question), like Ron G said, how to prove this one $$\cot x = \lim_{N\to +\infty} \left(\frac1x+\cdots+\frac1{x+N\pi}+\frac1{x-N\pi}\right)$$ Do you have any papers that can support that claim? $\endgroup$ – Venus Nov 11 '14 at 8:38
  • 3
    $\begingroup$ @Venus $$ \cot(x)={\Psi(1 - x/\pi) - \Psi(x/\pi) \over \pi} ={1 \over \pi}\,\left(1 - {2x \over \pi}\right)\sum_{n\ =\ 0}^{\infty}{1 \over \left(n + 1 - x/\pi\right)\left(n + x/\pi\right)} $$ $\endgroup$ – Felix Marin Nov 13 '14 at 19:31
  • 2
    $\begingroup$ @Venus Thanks. You may just take the logarithmic derivative of $$\displaystyle \sin x = x \prod_{n=1}^\infty \left( 1 - \frac{x^2}{(n\pi)^2} \right)$$ See here: dlmf.nist.gov/4.22 $\endgroup$ – Olivier Oloa Nov 13 '14 at 22:49
  • 1
    $\begingroup$ Thanks Oliver & @FelixMarin, very enlightening :-) $\endgroup$ – Venus Nov 14 '14 at 9:49
  • 2
    $\begingroup$ +1, This is exactly how I proved that identity, motivated by @orangekids' answer. And I am glad that finally a reference is available to me! Thank you! $\endgroup$ – Sangchul Lee Dec 8 '14 at 23:05

Please view this as an supplement of Olivier's answer.

I will derive a sufficient condition on the meromorphic function involved which allow one to apply a result similar to that in Olivier's answer.

Let $\phi(z)$ be any meromorphic function over $\mathbb{C}$ which

  1. preserve the extended real line $\mathbb{R}^* = \mathbb{R} \cup \{ \infty \}$ in the sense: $$\begin{cases}\phi(\mathbb{R}) \subset \mathbb{R}^*\\ \phi^{-1}(\mathbb{R}) \subset \mathbb{R}\end{cases} \quad\implies\quad P \stackrel{def}{=} \phi^{-1}(\infty) = \big\{\, p \in \mathbb{C} : p \text{ poles of }\phi(z)\,\big\} \subset \mathbb{R} $$

  2. Split $\mathbb{R} \setminus P$ as a countable union of its connected components $\,\bigcup\limits_{n} ( a_n, b_n )\,$. Each connected component is an open interval $(a_n,b_n)$ and on such an interval, $\phi(z)$ increases from $-\infty$ at $a_n^{+} $ to $\infty$ at $b_n^{-}$.

  3. There exists an ascending chain of Jordan domains $D_1, D_2, \ldots$ that cover $\mathbb{C}$, $$\{ 0 \} \subset D_1 \subset D_2 \subset \cdots \quad\text{ with }\quad \bigcup_{k=1}^\infty D_k = \mathbb{C} $$ whose boundaries $\partial D_k$ are "well behaved", "diverge" to infinity and $| z - \phi(z)|$ is bounded on the boundaries. More precisely, let $$ \begin{cases} R_k &\stackrel{def}{=}& \inf \big\{\, |z| : z \in \partial D_k \,\big\}\\ L_k &\stackrel{def}{=}& \int_{\partial D_k} |dz| < \infty\\ M_k &\stackrel{def}{=}& \sup \big\{\, |z - \phi(z)| : z \in \partial D_k \,\big\} \end{cases} \quad\text{ and }\quad \begin{cases} \lim\limits_{k\to\infty} R_k = \infty\\ \lim\limits_{k\to\infty} \frac{L_k}{R_k^2} = 0\\ M = \sup_k M_k < \infty \end{cases} $$

Given such a meromorphic function $\phi(z)$ and any Lebesgue integrable function $f(x)$ on $\mathbb{R}$, we have following identity: $$ \int_{-\infty}^\infty f(\phi(x)) dx = \int_{-\infty}^\infty f(x) dx \tag{*1} $$

In order to prove this, we split our integral into a sum over the connected components of $\mathbb{R} \setminus P$. $$\int_\mathbb{R} f(\phi(x)) dx = \int_{\mathbb{R} \setminus P} f(\phi(x)) dx = \sum_n \int_{a_n}^{b_n} f(\phi(x)) dx $$ For any connected component $( a_n, b_n )$ of $\mathbb{R} \setminus P$ and $y \in \mathbb{R}$, consider the roots of the equation $\phi(x) = y$. Using properties $(1)$ and $(2)$ of $\phi(z)$, we find there is a unique root for the equation $y = \phi(x)$ over $( a_n, b_n )$. Let we call this root as $r_n(y)$. Change variable to $y = \phi(x)$, the integral becomes

$$\sum_n \int_{-\infty}^\infty f(y) \frac{d r_n(y)}{dy} dy = \int_{-\infty}^\infty f(y) \left(\sum_n \frac{d r_n(y)}{dy}\right) dy $$ We can use the obvious fact $\frac{d r_n(y)}{dy} \ge 0$ and dominated convergence theorem to justify the switching of order of summation and integral.

This means to prove $(*1)$, one only need to show $$\sum_n \frac{d r_n(y)}{dy} \stackrel{?}{=} 1\tag{*2}$$

For any $y \in \mathbb{R}$, let $R(y) = \phi^{-1}(y) \subset \mathbb{R}$ be the collection of roots of the equation $\phi(z) = y$.

Over any Jordan domain $D_k$, we have following expansion

$$\frac{\phi'(z)}{\phi(z) - y} = \sum_{r \in R(y) \cap D_k} \frac{1}{z - r} - \sum_{p \in P \cap D_k} \frac{1}{z - p} + \text{something analytic}$$

This leads to $$\sum_{r \in R(y)\cap D_k} r - \sum_{ p \in P \cap D_k} p = \frac{1}{2\pi i}\int_{\partial D_k} z \left(\frac{\phi'(z)}{\phi(z) - y}\right) dz$$

As long as $R(y) \cap \partial D_k = \emptyset$, we can differentiate both sides and get

$$\begin{align} \sum_{r_n(y) \in D_k} \frac{dr_n(y)}{dy} &= \frac{1}{2\pi i}\int_{\partial D_k} z \left(\frac{\phi'(z)}{(\phi(z) - y)^2}\right) dz = -\frac{1}{2\pi i}\int_{\partial D_k} z \frac{d}{dz}\left(\frac{1}{\phi(z)-y}\right) dz\\ &= \frac{1}{2\pi i}\int_{\partial D_k}\frac{dz}{\phi(z) - y} \end{align} $$ For those $k$ large enough such that $R_k > 2(M+|y|)$, we can expand the integrand in last line as

$$\frac{1}{\phi(z) - y} = \frac{1}{z - (y + z - \phi(z))} = \frac{1}{z} + \sum_{j=1}^\infty \frac{(y + z - \phi(z))^j}{z^{j+1}}$$ and obtain a bound

$$\left|\left(\sum_{r_n(y) \in D_k} \frac{dr_n(y)}{dy} \right) - 1\right| \le \frac{1}{2\pi}\sum_{j=1}^\infty \int_{\partial D_k} \frac{(|y| + |z-\phi(z)|)^j}{|z|^{j+1}} |dz|\\ \le \frac{(M + |y|)L_k}{2\pi R_k^2}\sum_{j=0}^\infty\left(\frac{M+|y|}{R_k}\right)^j \le \frac{M + |y|}{\pi}\frac{L_k}{R_k^2} $$ Since $\lim\limits_{k\to\infty} \frac{L_k}{R_k^2} = 0$, this leads to

$$\sum_n \frac{dr_n(y)}{dy} = \lim_{k\to\infty} \sum_{r_n(y) \in D_k} \frac{dr_n(y)}{dy} = 1$$

This justifies $(*2)$ and hence $(*1)$ is proved. Notice all the $\frac{dr_n(y)}{dy}$ are positive, there is no issue in rearranging the order of summation in last line.

Back to the original problem of evaluating

$$\int_{-\infty}^\infty \frac{1}{1+(x+\tan x)^2} dx$$

One can take $\phi(z)$ as $z + \tan z$ and $f(x)$ as $\frac{1}{1+x^2}$. It is easy to see $\phi(z)$ satisfies:

  • Condition $(1)$ - For any $y \in \mathbb{R}$ and $u + iv \in \mathbb{C} \setminus \mathbb{R}$, we have $$\begin{align} \Im (\phi(u + iv) - y ) &= v + \Im\tan(u+iv) = v + \Im\frac{\tan u + i\tanh v}{1 - i\tan u\tanh v}\\ &= v + \tanh v\frac{1 + \tan^2 u}{1 + \tan^2 u\tanh^2 v} \ne 0 \end{align}$$

  • Condition $(2)$ - obvious.

  • Condition $(3)$. - Let $D_k$ to be the square $$D_k = \big\{\, u + v i \in \mathbb{C} : |u|, |v| \le k \pi \,\big\}$$ It is not hard to show $|z - \phi(z)| = |\tan z|$ is bounded above by $\frac{1}{\tanh k\pi}$ on $\partial D_k$.

Combine these, we can apply $(*1)$ and deduce

$$ \int_{-\infty}^\infty \frac{1}{1+(x+\tan x)^2} dx = \int_{-\infty}^\infty \frac{1}{1+x^2} dx = \pi $$

  • 2
    $\begingroup$ To be honest, I don't understand almost all of your answer, but it looks very cool, so +1. :-) $\endgroup$ – Venus Nov 11 '14 at 14:21
  • $\begingroup$ as a physicist i really have to get used to this "pure math style" proof, but after doing so i have to say: Really nice work! $\endgroup$ – tired Nov 11 '14 at 15:59
  • $\begingroup$ I'm thinking this theorem to solve my homework's problem: math.stackexchange.com/q/1017074/146687 Is it possible? $\endgroup$ – Venus Nov 11 '14 at 17:05
  • $\begingroup$ @Venus, I don't think so. To apply this theorem, the integrand need to have the form of composition of two function $f \circ \phi$. Furthermore, $\phi(x)$ need to looks like $x + $ something... $\endgroup$ – achille hui Nov 11 '14 at 17:22
  • 1
    $\begingroup$ Oh no... I'm in trouble now :-( $\endgroup$ – Venus Nov 11 '14 at 17:24

The Inverse Function Theorem gives us $$ \int_{-\infty}^{+\infty}f(g(x))\,\mathrm{d}x=\int_{-\infty}^{+\infty}\sum_{g(x)=\alpha}\frac1{\left|g'(x)\right|}\,f(\alpha)\,\mathrm{d}\alpha\tag{1} $$ If we integrate along squares, centered at the origin, whose sides are parallel to the $x$ and $y$ axes with length $2k\pi$, as $k\to\infty$, we get $$ \begin{align} \sum_{x+\tan(x)=\alpha}\frac1{1+\sec^2(x)} &=\frac1{2\pi i}\oint\frac{\mathrm{d}z}{z+\tan(z)-\alpha}\\[6pt] &=1\tag{2} \end{align} $$ Letting $g(x)=x+\tan(x)$, $(1)$ and $(2)$ give $$ \int_{-\infty}^{+\infty}f(x+\tan(x))\,\mathrm{d}x=\int_{-\infty}^{+\infty}f(x)\,\mathrm{d}x\tag{3} $$ Therefore, applying $(3)$ to $f(x)=\frac1{1+x^2}$ yields $$ \begin{align} \int_{-\infty}^{+\infty}\frac{\mathrm{d}x}{1+(x+\tan(x))^2} &=\int_{-\infty}^{+\infty}\frac{\mathrm{d}x}{1+x^2}\\[6pt] &=\pi\tag{4} \end{align} $$

  • $\begingroup$ Could you elaborate on the origin of the 1st line? I cannot figure out how to derive it from inverse function theorem. $\endgroup$ – pisco Aug 20 '17 at 6:58
  • $\begingroup$ Anyway, this is a very ingenious answer. It is interesting to see what happens when $g(x) = x - \tan x$, my method and your method both fail at some point, perhaps that integral does not admit a simple closed form. $\endgroup$ – pisco Aug 20 '17 at 7:03
  • $\begingroup$ @pisco125: break the real line into pieces where $g(x)$ is monotonic and apply the inverse function theorem on each piece. Each piece gives a term in the sum where $g(x)=\alpha$. $\endgroup$ – robjohn Aug 20 '17 at 15:49
  • $\begingroup$ @pisco125: Did you have a specific question using $g(x)=x-\tan(x)$? Note that $\frac1{|g'(x)|^2}=\frac1{\tan^2(x)}$. I haven't computed the corresponding sum for the integral, but I think it should be possible. It won't be $1$ in this case. $\endgroup$ – robjohn Aug 20 '17 at 21:29
  • $\begingroup$ In (1), the corresponding root of $g(x)=\alpha$ has to be real. However, $x-\tan x = \alpha$ in general has two complex roots. When using contour integration to calculate the sum in (2), those complex roots are involved. So the sum in (1) really involves the inverse of $x-\tan x$ to some extend, this complicated the matter. The above problem does not happen for $x+\tan x = \alpha$ because all its root are real. $\endgroup$ – pisco Aug 21 '17 at 3:31

This integral can also be evaluated by standard residue calculus.

Denote $f(z)=i- \tan z - z$, then $$g(z) :=\frac{1}{(z+\tan z)^2+1} = \frac{-1}{f(z)f(-z)}$$ Note that if $f(z_0) = 0$, then $f(-z_0) = 2i$. Using the identity: $$\tan(x+yi) = \frac{\sin(2x)}{\cosh(2y)+\cos(2x)} + \frac{\sinh(2y)}{\cosh(2y)+\cos(2x)}i $$ it can be seen that $f(z) = 0$ has no root in the lower half plane. Also note that all zeroes of $f(z)$ are simple.

Let $R_n$ denote the rectangle with vertices $-n\pi, n\pi, n\pi (1+i), n\pi (-1+i)$. $\tan z$ is uniformly bounded on $R_n$ except the real axis. Denote the inside of the rectangle by ${R_n}'$. We have $$\int_{R_n} g(z) dz \to I:=\int_{-\infty}^{\infty} \frac{1}{(x+\tan x)^2+1} dx \quad \text{ as }\quad n\to \infty$$

Thus $$\begin{aligned} I &= 2\pi i \lim_{n\to\infty}\left[\sum_{\substack{f(z_0)=0 \\ z_0\in {R_n}'}}\text{Res}\left[g(z),z_0\right] + \sum_{\substack{f(-z_1)=0 \\ z_1\in {R_n}'}}\text{Res}\left[g(z),z_1\right] \right] \\ &= 2\pi i \lim_{n\to\infty}\left[\sum_{\substack{f(z_0)=0 \\ z_0\in {R_n}'}}\frac{-1}{f(-z_0)f'(z_0)} - \sum_{\substack{f(-z_1)=0 \\ z_1\in {R_n}'}}\frac{-1}{f(z_1)f'(-z_1)} \right] \\ &= -\pi \lim_{n\to\infty}\left[\sum_{\substack{f(z_0)=0 \\ z_0\in {R_n}'}}\frac{1}{f'(z_0)} -\underbrace{\sum_{\substack{f(-z_1)=0 \\ z_1\in {R_n}'}}\frac{1}{f'(-z_1)}}_{=0} \right] \\ &= -\pi \lim_{n\to\infty} \sum_{\substack{f(z_0)=0 \\ z_0\in {R_n}'}}\frac{1}{f'(z_0)} \end{aligned}$$ the sum in underbrace is zero becuase $f(z)$ has no root in the lower half plane.

Let $S_n$ denote the square with vertices $n\pi(\pm 1 \pm i)$. Then $$\int_{S_n} \frac{1}{f(z)} dz = \int_{S_n} \frac{1}{i-\tan z-z} dz = 2\pi i \sum _{\substack{f(z_0)=0 \\ z_0 \in R'_n}} \frac{1}{f'(z_0)}$$

Hence $$\int_{S_n} \left( \frac{1}{i-\tan z -z }+\frac{1}{z} \right) dz = 2\pi i \left[1 + \sum _{\substack{f(z_0)=0 \\ z_0 \in R'_n}} \frac{1}{f'(z_0)} \right]$$ Because $\tan z$ is uniformly bounded on $S_n$, the integrand in the LHS is of $O(1/z^2)$, so it approaches $0$ as $n\to\infty$. Hence $$\lim_{n\to\infty}\sum_{\substack{f(z_0)=0 \\ z_0\in {R_n}'}}\frac{1}{f'(z_0)} = -1$$ thus $I=\pi$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.